An Application of Analytic Hierarchy Process and Entropy Weight Method in Food Cold Chain Risk Evaluation Model - Shen, Yuyan; Liao, Kaicheng (Frontiers in Psychology, 2022)
If not well identified and controlled, the risks in the cold supply chain, which is systematic engineering, will directly lead to food safety incidents. There exists a lack of systematic classification in the present risk evaluation of the cold supply chain, not to mention the concrete quantitative analysis of the influences of risk factors on the cold supply chain. To accurately evaluate some unknown risks that exerted fluctuating influences and resulted in great losses, the risks were evaluated on the basis of an expert system, the weight assignment was performed using the ordered weighted averaging (OWA) operator, and the Logistic diffusion-convergence model was constructed for the cold supply chain risks to evaluate and control the supply chain risks. First, the risk identification and classification of the food cold supply chain were conducted. Second, the evaluation method integrating the expert system and OWA operator-based weight assignment was used to assign weight to each risk index and conduct the risk assessment, and the risk values were obtained and ranked. Last, the index values of the quantitative analysis were given by combining the IoT scenario from the aspect of risk control, the Logistic diffusion-convergence model of food cold supply chain risks under the IoT scenario was proposed, and the concrete risk management and control measures were put forward on the basis of the model calculation results. Results show that the evaluation method combining the expert system knowledge base and OWA operator can effectively depict and process the evaluation information in the risk ranking and more rapidly and effectively solve the problems of the supply chain risks on a certain basis.